The regulatory response to the financial crisis - Goodhart, Charles A. E. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2010)
This text explains that there are two main attributes that a bank needs to remain in business during a period of turmoil, liquidity to enable it to pay its debts when due, and capital, to absorb losses - both have been insufficient.
Includes bibliographical references
BSBA
Keywords: Financial crises; Banks and banking, Central; Financial services industry -- Risk management; Banks and banking -- State supervision